2018
DOI: 10.1101/267286
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Collective motion conceals fitness differences in crowded cellular populations

Abstract: Many cellular populations are tightlypacked, for example microbial colonies and biofilms [39,10,41], or tissues and tumors in multi-cellular organisms [11,29]. Movement of one cell inside such crowded assemblages requires movement of others, so that cell displacements are correlated over many cell diameters [28,6,31]. Whenever movement is important for survival or growth [15,34,38,9], such correlated rearrangements could couple the evolutionary fate of di↵erent lineages. Yet, little is known about the interpla… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 40 publications
4
30
0
Order By: Relevance
“…The shape of the emerging super sector has previously been linked to the relative growth rate advantages 35 . Similar observations have been made in studies focusing on the mechanical forces shaping the spatial patterns of mutant strains with relative growth rate differences during range expansion 17,18 . In both cases, cells having a growth rate disadvantage managed to stay at the colony periphery through mechanical interactions, and shoving of the surrounding faster growing cells.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The shape of the emerging super sector has previously been linked to the relative growth rate advantages 35 . Similar observations have been made in studies focusing on the mechanical forces shaping the spatial patterns of mutant strains with relative growth rate differences during range expansion 17,18 . In both cases, cells having a growth rate disadvantage managed to stay at the colony periphery through mechanical interactions, and shoving of the surrounding faster growing cells.…”
Section: Discussionsupporting
confidence: 76%
“…Within such highly constrained systems, scenarios emerge in which a few cells contribute disproportionally to the long term community biomass 10 supporting the notion of "survival of the luckiest". Evidence in the form of genetic segregation of initially mixed communities is observed frequently in colonies growing on surfaces [11][12][13][14][15][16][17][18] , or observations of detrimental mutations accumulating at the assemblage periphery that are rapidly lost in homogeneous environments such as liquid cultures 19 . During sessile growth, bacterial cells are essentially fixed in space and depend on diffusional fluxes dictated by heterogeneous nutrient landscapes (governed by the surface and their neighbors) that ultimately shape the resulting bacterial assemblage 6 .…”
mentioning
confidence: 99%
“…They showed that the probability that a mutant spreads in the population can be related to summary statistics characterizing cell alignment and the front roughness. In parallel to our investigation, Kayser et al ( 19 ) showed that the mechanical interaction between a faster-growing and a slower-growing strain can cause the prolonged survival of the slower-growing one at the colony frontier, a process that we have investigated in a different geometry and from a different modeling perspective.…”
supporting
confidence: 57%
“…Of particular interest may be methods for an enhanced characterization of jamming and folding in developing tissues (Mongera et al, 2018;Nnetu et al, 2012;Petridou et al, 2019;Trushko et al, 2018). Furthermore, flow perturbations could be used to mimic tissue-jamming dynamics with cellular systems of reduced complexity (Kayser et al, 2018). Also, highly advantageous would be physical methods to enhance the transport of metabolites and waste products within 3D tissue cultures.…”
Section: Physically Assisted Guidance Of Developmentmentioning
confidence: 99%